Search for lepton flavor-violating decay modes B 0 → K *0 τ ± ℓ ∓ (ℓ = e, μ) with hadronic B-tagging at Belle and Belle II - The Belle and Belle II collaboration; I. Adachi; Y. Ahn; H. Aihara; N. Akopov; S. Alghamdi; M. Alhakami; A. Aloisio; K. Amos; M. Angelsmark; N. Anh Ky; C. Antonioli; et al. (Journal of High Energy Physics)
Abstract We present the results of a search for the charged-lepton-flavor violating decays B 0 → K *0 τ ± ℓ ∓, where ℓ ∓ is either an electron or a muon. The results are based on 365 fb −1 and 711 fb −1 datasets collected with the Belle II and Belle detectors, respectively. We use an exclusive hadronic B-tagging technique, and search for a signal decay in the system recoiling against a fully reconstructed B meson. We find no evidence for B 0 → K *0 τ ± ℓ ∓ decays and set upper limits on the branching fractions in the range of (2.9–6.4)×10 −5 at 90% confidence level.